Spare Roof Technique: A Middle Third New Technique - Ferreira, Miguel Gonçalves; Monteiro, Daniel; Reis, Claudia; Sousa, Cecilia Almeida e (Facial Plastic Surgery, 2016)
To our knowledge, the spare roof technique (SRT) is the first technique that is based on a complete skeletonization/preservation of the upper lateral cartilages. This technique is used to keep the natural roof of the nose's middle third, while dehumping and/or correcting the crooked septum. From January 2014 till March 2015, a total of 40 rhinoplasties were performed through the SRT: 28 reduction rhinoplasties, 6 complex crooked noses (with extracorporeal septoplasty), and 6 mixed cases. The SRT is an excellent middle third technique. The natural roof was kept and fitted the accurate new position in almost all cases with no surgical complexity. It is an easy technique with many applications and it is also very useful in the classical humpectomy of the Caucasian nose and correction of the crooked nose.
Keywords: rhinoplasty; humpectomy; dehump; upper lateral cartilages; spare roof technique